Erythema multiforme major in a 10-year-old boy. Challenges in diagnosis and treatment. - Jerkovic Gulin, S.; Starcea, M.; Alexoaie, M.; Chiriac, A. (European Journal of Pediatric Dermatology, 2018)
The Authors reported a case of erythema multiforme major characterized by marked diagnostic and therapeutic difficulties. They were not able to highlight clinically or through laboratory examinations a responsible virus infection. Although started two weeks after the onset of the disease, acyclovir seemed to improve the eruption. However, the Authors underline that the diseases regresses spontaneously.